Mathematical Models for Analysis the Impact of Institutional Quality and Multilateral Financial Institutions on the Success of Green PPP Projects - Wu-Yan Li; Ruo-Yu Chen; Ming Ma (Journal of Function Spaces)
Green PPP projects are of great significance to green infrastructure construction and green economic development. This study analyzes 552 Green PPP projects related to sewage treatment and clean energy in African countries during 2005-2019 to determine how institution quality and multilateral financial institutions influence Green PPP projects’ success. We find that (1) successful (failed) Green PPP projects experience increase (decrease) new Green PPP projects’ success rate. (2) Higher private capital risk-taking degree increases the likelihood of failure. (3) Institution quality affects project success through a mixed effect on private capital’s risk-taking degree: rule of law, government effectiveness, control of corruption, and regulatory quality positively promote private capital’s risk taking; voice has an opposite effect. (4) Multilateral financial institutions’ participation in Green PPP projects promotes higher private capital risk taking.